2014
DOI: 10.1186/1746-160x-10-46
|View full text |Cite
|
Sign up to set email alerts
|

Lingual orthodontic treatment duration: performance of two different completely customized multi-bracket appliances (Incognito and WIN) in groups with different treatment complexities

Abstract: IntroductionThe occurrence of side-effects of fixed orthodontic therapy, such as white-spot lesions and root resorption, are known to be significantly more frequent with increasing duration of treatment. Multi-bracket treatment should be as short as possible, in order to minimize the risks of collateral damage to teeth. The aim of this non-randomized clinical trial was to compare treatment duration with each of two types of customized lingual orthodontic appliances (Incognito, 3 M-Unitek; WIN, DW LingualSystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…In another study, the number of lost brackets during the first year of treatment was found to be similar for lingual and labial appliances (32). Finally, a recent retrospective study compared two different lingual systems and showed that treatment The number of caries that formed (buccal: n = 16, lingual: n = 1) or progressed (buccal: n = 21, lingual: n = 7) was higher in buccal compared to lingual lesions (P = 0.01); the overall increase in caries extent/total lesion area was 10.6 times higher on buccal surfaces in a subject than on lingual surfaces (P < 0.05) (18). The results of these investigations, however, have to be interpreted taken into account the possibility of the influence of the various biases on the study outcomes.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In another study, the number of lost brackets during the first year of treatment was found to be similar for lingual and labial appliances (32). Finally, a recent retrospective study compared two different lingual systems and showed that treatment The number of caries that formed (buccal: n = 16, lingual: n = 1) or progressed (buccal: n = 21, lingual: n = 7) was higher in buccal compared to lingual lesions (P = 0.01); the overall increase in caries extent/total lesion area was 10.6 times higher on buccal surfaces in a subject than on lingual surfaces (P < 0.05) (18). The results of these investigations, however, have to be interpreted taken into account the possibility of the influence of the various biases on the study outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…and N.G.) evaluated several items according to a modified quality assessment tool designed based on Newcastle-Ottawa scale (18), relevant guidelines of the Cochrane Handbook for Systematic Reviews of Interventions Version 5.1.0 (15), and the GRADE approach (16).…”
Section: Quality Assessment Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment duration of both labial and lingual fixed appliances could be affected by replaced brackets and/or bands and missed appointments. 24 The treatment duration of lingual appliances is similar to buccal appliances, 25 but with the invisible characteristics of lingual appliances, patients seem to be less worried about the treatment duration. Another consideration is that lingual appliance wearers had higher incomes than buccal appliance wearers ( P <0.001; Supplementary Table ), and patients with better financial conditions might be less anxious amid this pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…However, as there has also been an increased use of lingual appliances in more complex treatments in adolscents [17], combination of lingual appliances with a Herbst type functional appliance are a common element of the contemporary orthodontic spectrum of therapy [1820]. Similarly to vestibular Herbst derivatives, the fixation of Herbst telescopes in common lingual appliances (Incognito, 3 M Unitek, TOP-Service für Lingualtechnik, Bad Essen, Germany) is achieved by bands on the lower canines and upper first molars, which are simultaneously provided with a lingual bracket [21].…”
Section: Introductionmentioning
confidence: 99%